Comparison of protein extraction methods from excess activated sludge. (June 2020) - Gao, Jianlei; Weng, Wei; Yan, Yixin; Wang, Yingchun; Wang, Qikun
Abstract: In this study, we used chemical methods (acid-thermal (AT) and alkaline-thermal (AKT)), enzymatic methods (single enzyme (SE) and composite enzyme (CE)) and assisted enzymatic methods (ultrasonic assisted enzyme (USE) and thermal assisted enzyme (TE)) to extract proteins from excess activated sludge. The advantages and applicability of each method were compared and analyzed in terms of their protein extraction rate (RP ), energy consumption, material consumption and cost, protein hydrolysates and sludge dewatering performance. The results showed that the RP of the chemical methods were more than 75%, which were much higher than those of the enzymatic methods. Moreover, the RP of SE was significantly strengthened by physical means (ultrasonic or thermal), and the average RP was increased by more than 39% compared with that of enzymatic methods. The energy consumption analysis showed that chemical methods consumed significantly more energy than the enzymatic methods. Further analysis of enzymatic methods and assisted enzymatic methods revealed that although the energy consumption of USE was similar to that of SE, its enzyme consumption and cost were lower. In addition, the proteins extracted by USE had a high content of amino acids, which was suitable for the preparation of animal feed. The proteins extracted by AKT had a high content of polypeptides, which was beneficial to the preparation of a protein foaming agent. Furthermore, the sludge dewatering performance after hydrolyzation by the six hydrolysis methods was significantly improved, which was beneficial to the separation of proteins. Highlights: Extraction of protein from excess sludge by six hydrolysis methods. The protein extraction rate by AT was the highest. The protein extracted from AKT had a high content of polypeptides. USE had the advantages of low cost and enzyme consumption. The sludge dewatering performance after hydrolyzed was significantly improved.